Insilico analysis of pb1 protein of influenza a virus (Funded Work) - K.AKILA (International Journal of Pharma and Bio Sciences, 2017)
The influenza A virus affected a worldwide pandemic outbreak in 2009. Due to the reoccurrence of H1N1 pandemic there is a necessity to study the H1N1 proteins. Influenza A virus is a lipid-enveloped orthomyxovirus and a origin of human disease by strains that arise through periodic variation and through pandemic infection causing from viral adaptation that introduces new influenza viruses into the human population. Similar other influenza viruses cause a respiratory infection that spreads from individual to individual by coughing and sneezing. The current study focuses PB1 protein of the Influenza A virus. This protein is the subunit of polymerase protein. It is involved in both transcription and replication of the genome RNA. It has 757 amino acids. This work involves the targeting of valine at 715th position in the protein sequence which is the most mutable site in the sequence as inferred from the literature. The site was replaced by hydrophilic amino acid in the 715th position of the sequence instead of hydrophilic amino acid. Due to the most harmful effect of the mutated protein, the current work aimed at designing the 3D structure and the predicted structure was validated. This modelled structure will aid to design a drug in future.